2016
DOI: 10.1177/0271678x15625077
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of adenosine deaminase in the striatum

Abstract: Adenosine deaminase (ADA) is a ubiquitous enzyme that catabolizes adenosine and deoxyadenosine. During cerebral ischemia, extracellular adenosine levels increase acutely and adenosine deaminase catabolizes the increased levels of adenosine. Since adenosine is a known neuroprotective agent, adenosine deaminase was thought to have a negative effect during ischemia. In this study, however, we demonstrate that adenosine deaminase has substantial neuroprotective effects in the striatum, which is especially vulnerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
(138 reference statements)
1
8
0
2
Order By: Relevance
“…In this experiment, we referred to a method used in previous reports. To create an ischemic condition, Tamura et al ( 26 ) exposed adult rat corticostriatal brain slices to 30 min of hypoxia (N 2 95%-CO 2 5%) with temporary oxygen/glucose deprivation. Then, after 1 h of oxygenated (95% O 2 -5% CO 2 ) incubation with aCSF, they found that the protein expression of light chain 3-II had increased more in the ischemia group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this experiment, we referred to a method used in previous reports. To create an ischemic condition, Tamura et al ( 26 ) exposed adult rat corticostriatal brain slices to 30 min of hypoxia (N 2 95%-CO 2 5%) with temporary oxygen/glucose deprivation. Then, after 1 h of oxygenated (95% O 2 -5% CO 2 ) incubation with aCSF, they found that the protein expression of light chain 3-II had increased more in the ischemia group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…After the 30 - min treatment, the sections in both groups were oxygenated with 5% CO 2 -95% O 2 for 3 h at room temperature (23°C ± 1°C) (see Fig. 6 B ) ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…There are two main metabolic pathways of adenosine: (a) it becomes inosine under the action of adenosine deaminase (ADA) then generates hypoxanthine and hypoxanthine nucleotides through nucleosidases and finally becomes uric acid, which is an end product of purine derivatives in human metabolism . (b) Most adenosine enters the cell via a bidirectional balance transporter, and the adenosine kinase (ADK), which generates AMP by phosphorylation in central cells, only exists in the astrocytes.…”
Section: Adenosine Production and Metabolismmentioning
confidence: 99%
“…У тканинах гемоглобін залишає необхідний для дихання газ, замінюючи його вже відпрацьованим вуглекислим газом, і відносить назад до легеневих альвеол. Виведення гемоглобіном вуглекислоти дозволяє знижувати рівень кислотності в організмі, тим самим, підтримуючи рівновагу pH і виконуючи функцію регулятора [9,10].…”
Section: Beastdoctor24@gmailcomunclassified